Analisis Perbedaan Kinerja Keuangan Sebelum dan Sesudah Mengakuisisi - Tiara Putri Permana; Riyanti; Budi Wahyudi; Dini Dwi Ermawati (Forum Kerjasama Pendidikan Tinggi, 2025)
An acquisition is a merger of two companies in which the acquiring company buys part of the shares of the acquired company, so that the management control of the acquired company is transferred to the acquiring company, while the two companies each continue to operate as an independent legal entity. The purpose of the acquiring company acquiring a company includes expanding the company's business, increasing the company's synergy, etc. In this case, the purpose of PT Sumber Alfaria Trijaya, Tbk acquiring PT Global Loyalty Indonesia is to strengthen the synergy of the joint member point program (membership program) developed by PT Global Loyalty Indonesia. This study aims to analyze the financial performance before and after the acquisition. The subject of this research is PT Sumber Alfaria Trijaya, Tbk. which acquired PT Global Loyalty Indonesia. Descriptive and quantitative research methods using the Financial Ratio Analysis method, namely Liquidity, Solvency, Activity, and Profitability. Data analysis techniques use normality tests, descriptive statistical tests and different tests. The data used in this study are the financial statements of PT Sumber Alfaria Trijaya, Tbk. before the acquisition (2015-2018) and after the acquisition (2020-2023). The results showed that the majority of ratios did not differ between before and after the acquisition, which means that the purpose of PT Sumber Alfaria Trijaya, Tbk acquiring PT Global Loyalty Indonesia has not been fully successful during the study period.